Bacteriophage- induced reduction in Salmonella Enteritidis counts in the crop of broiler chickens undergoing preslaughter feed withdrawal - Marietto Goncalves, Guilherme Augusto [UNESP]; Donato, Tais Cremasco [UNESP]; Sampaio Baptista, Ana Angelita [UNESP]; Oliveira Correa, Isadora Mainieri de [UNESP]; Ornellas Dutka Garcia, Keila Carolina [UNESP]; Andreatti Filho, Raphael Lucio [UNESP] (Oxford University Press, 2014)
Salmonella food poisoning is a public health problem. Feed withdrawal from broiler chickens before slaughter can favor the multiplication of Salmonella in the cecum and crop of contaminated animals and subsequently lead to contamination of carcasses in the processing plant. In the present study, a cocktail of lytic bacteriophages isolated from sewage water was orally administered to 45-d-old broiler chickens 1 h after they received an oral dose of 107 cfu/mL Salmonella enterica subspecies enterica serotype Enteritidis. Immediately after phage administration and 30 min, 1, 3, 6, and 12 h thereafter, groups of chicken were killed. Ceca and crops were analyzed for the presence of Salmonella. At 3 h posttreatment, there were 103 cfu/g and 101 cfu/g of cecal and crop suspension, respectively. At 6 h after treatment, the number of Salmonella was 103 cfu/g in the cecal suspension, but below the detection limit in the crops. our results suggest that bacteriophage therapy may be able to reduce the contamination of chicken carcasses by reducing the preslaughter load of Salmonella in the birds.
Keywords: bacteriophage therapy; Salmonella Enteritidis; public health; biotechnology